Advanced Medical Data Security with Smart Cards, QR Codes & Aadhar - Kakade, Mangesh; Vaidya, Sorabh; Andhale , Shubham; Mandlik, Shital Y. (International Journal of Recent Advances in Engineering and Technology, 2025)
In an era where healthcare data is increasingly stored and transmitted over wireless networks, ensuring the privacy and security of medical information has become a critical challenge. This project focuses on developing an advanced framework that enhances medical data privacy and security through the integration of smart card technology and QR codes, leveraging Aadhar card authentication mechanisms. The proposed framework utilizes smart cards to securely store patient information and facilitate access control, while QR codes provide a user-friendly method for data sharing and verification. By incorporating Aadhar card authentication, the system ensures robust identity verification, preventing unauthorized access to sensitive medical data. The framework aims to address vulnerabilities associated with wireless networks, offering a comprehensive solution that safeguards patient privacy while maintaining the efficiency of healthcare services. Through a combination of innovative technologies, this project seeks to create a secure environment for managing medical data, ultimately fostering trust in digital health solutions and protecting patients’ rights to privacy.